Fabrication techniques and properties of scaffolds - Sultana, N. (Springer Verlag, 2013)
The development of porous materials for use as scaffolds for the sustained 3D growth of tissue is a fast growing area in TE that has attracted commercial interest to a large extent. To fabricate both polymer scaffold and composite scaffold, many techniques are available. By using proper technique, the porous structure of polymeric and composite scaffolds could be controlled by varying the processing or formulation parameters. It is often necessary to modify the surface properties of biomaterials without changing the bulk attributes as a biomaterial rarely possess good surface characteristics suitable for bone tissue engineering. This chapter reviews the various existing methodologies to fabricate scaffolds and to modify the surface properties of scaffolds. It also discusses the study of interactions between tissues and biomaterials.